Conditions for the Use of Zero-Rating Packages in the Light of the Principle of Net Neutrality - Milczarek, Ewa (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The subject of the article is an analysis of the impact of zero-rating packages on the principle of net neutrality. This issue is of significant importance for the telecommunications and internet services market in the EU. The result of the research is to determine whether and under what conditions communication service providers can use zero-rating packages. Using a case study based on the case law of the European Court of Justice, the author considers the relationship between the essence of net neutrality and its role in the European axiological heritage.